(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Meibomian gland dysfunction (MGD) is a chronic, diffuse abnormality of the meibomian glands, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion. Diabetic polyneuropathy can be a cause of MGD. Purpose: To improve the efficacy of diagnosis of MGD in patients with severe complications of diabetic polyneuropathy. Materials and Methods: Standard ophthalmological examination, the Schirmer’s test before and 2 hours after eyelid compression, the Norn’s test, the OPI test, a compression test, an IVAD test, contact meibography with green filter were performed. Severe complications of diabetic polyneuropathy (N3 stage) were recorded in 25 patients (50 eyes). A control group consisted of 97 persons (194 eyes) without diabetes. Results and Discussion: The Schirmer’s test was 2.7 times reduced in patients with N3 stage (4.83 mm) in comparison with that in the control group (12.82) (p<0.001). The Norn’s test was 4.8 times lower in patients with N3-stage (3.45 sec) than in patients without diabetes (9.48 sec) (p<0.001). The OPI test in patients with N3 stage was 1.9 times lower than that in the control group, (p<0.001). The Schirmer’s test in patients with N3 were 1.2 times higher after compression than before it (p<0.05). According to meibography, in patients with N3, loss area of the meibomian glands corresponded to stage 4. Conclusions: The patients with stage N3 had MGD stage 3 (44 %) and 4 (40 %), while the first stage of MGD was not identified in any patient.